306 Pre-hospital care in Oman: results from hospital based trauma registry. (1st September 2016) - Mehmood, Amber; Allen, Katharine A; Salami, Joseph; Kashmiri, Ammar Al; Busaidi, Ali Al; Stevens, Kent; Hyder, Adnan A
Abstract : Background: Many injury victims die before reaching a hospital due to inadequate pre-hospital care and transport. Prompt emergency care can save lives and prevent disabilities but the inconsistent availability of formal Emergency Medical Services (EMS) makes it challenging. This is the case even in some high-income developing countries like Oman. For this study we analysed the trauma registry data from two large hospitals of Oman to understand the pre-hospital and hospital based emergency care in a rapidly developing country in the Arab Gulf. Methods: The data was collected from Khoula and Nizwa hospitals between November 2014 and April 2015. All patients admitted through the emergency department with a history of trauma were included. Information about mechanism of injury, mode of transport, time interval between injury and hospital, pre-hospital care and emergency department (ED) disposition was collected. Results: 2, 340 patients were received in the ED during the study period. The majority (74%) were males, with a mean age 27 years. Transport injuries and falls accounted for 70% of all injuries. The most common mode of transport was private car (43%); only 13% of patients were transported via EMS. Only 30% of cases were transported to the hospital within an hour of injury; median transport time was 2.53 hours. Only 27% of patients received some form of pre-hospital care. Twenty-three ED deaths were recorded. Mean ED length of stay was 16.35 hours. In the study population, injury severity score in 85% of cases was ≤9, mean revised trauma score was 7.6382 and overall mortality ratio was 2.35%. Conclusion: Despite rapidly developing health care services in the urban parts of Oman, EMS utilisation is low. Patients presenting to the hospital are those who have less severe injuries and thus have better chances of survival. A better-organised EMS system may provide a prompt transport and appropriate triage to patients with severe injuries.